The effect of spiritual/religious intervention on inner strength in women with breast cancer - Safoora Davari; Isaac Rahimian Boogar; Siavash Talepasand; Mohamad Reza Evazi (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: Cancer is accompanied with psycho-social aspects that require complementary spiritual/religious interventions along with medical interventions for treating these patients. Thus, the present study aimed at examining the effect of religious/spiritual interventions on the inner strength of women suffering from breast cancer. Method: This study adopted a quasi-experimental design with pretest and posttest in three groups-namely experimental, placebo, and control. Convenience sampling was used to select 41 participants out of the women referring to Omid radiotherapy and chemotherapy center, and Bandar-Abbas specialized clinics from Mehr 95 through Tir 96. The participants were randomly assigned to experimental (14 persons), placebo (14 persons), and control (13 persons) groups. The experimental group underwent individual spiritual/religious intervention in 10 sessions and the placebo group was exposed neutral training, while the control group received no treatment. Data were collected by questionnaires on inner strength and demographic features in pretests and posttests and analyzed through repeated measures multivariate analysis of variance. All ethical issues were observed in this study and the researchers declared no conflict of interests. Results: The findings indicated significant differences between the intervention group and placebo/control group in terms of the rise of inner strength, and the subscales of Engagement, Connectedness, Anguish and Searching, and Movement (p<0.05). Conclusion: Based on the findings, as a complement to typical medical cares, individual spiritual/religious intervention has positive effects on internal power and its subscales in women suffering from breast cancer. It is possible to use this intervention to enhance the psychological status in cancer treatment. For downloading the full-text of this article please click here. Please cite this article as: Davari S, Rahimian Boogar I, Talepasand S, Evazi MR. The effect of spiritual/religious intervention on inner strength in women with breast cancer. J Res Relig Health. 2019; 4(5): 27- 44.